Technical, Allocative, and Economic Efficiencies of Rice cultivation - Budi Setiawan, Avi; Ari Bowo, Prasetyo (JEJAK: Jurnal Ekonomi dan Kebijakan, 2015)
This research aims to analyse efficiency of rice cultivation at Grobogan regency. This regency was chosen as the research area because it gave major contribution in the rice crop in Central Java province and it has become national food stock. There are three efficiency analyses: technical, allocative, and economic analyses. The result showed that the farmers in Grobogan regency were still not efficient both technically and economically in growing the rice.The inefficiency was driven due to the overuse of input. The excessive use of production factor caused the decrease of soil quality. It then made the production of the crop less optimal. Besides, the use of excessive inputs caused decreasing return to scale because of the generated marginal output was less than the marginal input.Â